Perkembangan Rasa Ingin Tahu Mahasiswa melalui Pengintegrasian Nilai Islami dalam Pembelajaran Matematika - Khairatul Ulya; Zikra Hayati (Universitas Syiah Kuala, 2020)
Islamic values are the basis of reference in efforts to improve students' character and attitudes. The low value of students character is a scourge of today's problems. This study aims to determine the development of students' curiosity through the integration of Islamic values in mathematics learning. This research is a qualitative exploratory. Data were collected by using interviews and observations. The instruments used were observation sheets and interview guidelines to determine the development of curiosity. The subjects were three students at the Mathematics Education Department, FTIK IAIN Langsa. The results showed that two subjects have developed four indicators of curiosity: namely always asking questions, not accepting something learning as boring, showing listening, speaking, reading and writing skills and showing pleasure in learning. Meanwhile, there is one subject but there is one subject that does not develop curiosity on indicators showing listening, speaking, reading and writing skills. The results of study support theories stating that the integration of learning mathematics and Islamic values has a positive impact on students character. Therefore, this research can be considered for the Faculty of Education to further develop learning that integrating science and Islamic values in curriculum development as an effort to develop student character.